The NHS Bowel Cancer Screening Program: current perspectives on strategies for improvement - Koo S; Neilson LJ; Von Wagner C; Rees CJ (Dove Medical Press, 2017)
Sara Koo,1 Laura Jane Neilson,1 Christian Von Wagner,2 Colin John Rees1,3,4 1Department of Gastroenterology, South Tyneside District Hospital, South Shields, 2Health Behaviour Research Centre, University College London, London, 3School of Medicine, Pharmacy and Health, Durham University, Stockton on Tees, 4Northern Institute for Cancer Research, Newcastle University, Newcastle upon Tyne, UK Abstract: Colorectal cancer (CRC) is the third most common cancer in the UK. The English National Health Service (NHS) Bowel Cancer Screening Program (BCSP) was introduced in 2006 to improve CRC mortality by earlier detection of CRC. It is now offered to patients aged 60–74 years and involves a home-based guaiac fecal occult blood test (gFOBt) biennially, and if positive, patients are offered a colonoscopy. This has been associated with a 15% reduction in mortality. In 2013, an additional arm to BCSP was introduced, Bowelscope. This offers patients aged 55 years a one-off flexible sigmoidoscopy, and if several adenomas are found, the patients are offered a completion colonoscopy. BCSP has been associated with a significant stage shift in CRC diagnosis; however, the uptake of bowel cancer screening remains lower than that for other screening programs. Further work is required to understand the reasons for nonparticipation of patients to ensure optimal uptake. A change of gFOBt kit to the fecal immunochemical tests (FIT) in the English BCSP may further increase patient participation. This, in addition to increased yield of neoplasia and cancers with the FIT kit, is likely to further improve CRC outcomes in the screened population. Keywords: colorectal cancer, flexible sigmoidoscopy screening, Bowelscope, CT colongraphy, fecal immunochemical tests, gFOBt screening, uptake, quality in colonoscopy